A high stability GO nanofiltration membrane preparation by co-deposition and crosslinking polydopamine for rejecting dyes. (25th February 2022) - Liu, Yulong; Huang, Zhonghua; Zhang, Zhen; Lin, Xiaolu; Li, Qunxia; Zhu, Yihang
Abstract: In order to improve the stability of nanofiltration membrane in separation and purification, a novel polyelectrolyte multilayer nanofiltration membrane was facilely prepared by co-deposition of polydopamine (PDA) and polyethyleneimine (PEI) on the polyethersulfone (PES) ultrafiltration membrane substrate, followed by immersing graphene oxide (GO) solution, and crosslinking PDA. The modified surfaces were characterized using scanning electron microscopy (SEM) and atomic force microscopy (AFM), water contact angle, their saline flux and ability to reject salt and dye were determined. The results also exhibited salt rejection ability as Na2 SO4 > K2 SO4 > MgSO4 > NaCl > KCl > MgCl2, suggesting the higher rejection of divalent anion. Also, the retention order of the dye by the GO modified membrane is DY86 > DB19 > AG27 > DY142 > DB56 > AR151 > VB5, indicating that the GO modified membrane has better rejection of negatively charged dyes as well as higher molecular weight dyes. Ethanol and hypochlorite resistance tests under different pH conditions showed the membranes coated GO enhanced stability in regard to salt rejection properties. Significantly, the anti-biological test confirmed the growth rate of microalgae on the GO introduced membrane was decreased greatly due to enhanced stability and lower roughness. HIGHLIGHTS: This work has successfully prepared the (PDA@PEI/GO/PDA)/PES membrane by dip coating and chemical crosslinking. The membrane has a good effect on the removal of divalent ions and better rejection of negatively charged dyes as well as higher molecular weight dyes. The obtained membrane has high stability and excellent anti-biological pollution performance. Graphical Abstract